Does competition from for-profit firms raise wages for preschool workers? - Karin Edmark; Lovisa Persson (Research Institute of Industrial Economics (IFN), 2025)
We study the wage effects of an expansion of for-profit preschools in Sweden, which followed after a reform in 2006 removed municipalities' right to veto private entry. The expansion decreased preschool employers' monopsony power by increasing the number of alternative employers. We use a differences-in-differences event study design to evaluate the impact on preschool workers' wages, and find no evidence that wages were affected. In the context that we study, the absence of an upward wage effect may be explained by the entering for-profit firms' propensity to hire less qualified, lower-paid staff, and workers from other sectors of the economy than the preschool sector.
Keywords: H44; I2; J31; J42; 330; monopsony power; for-profit provision; preschool workers; gender gap